Determination of influences on support strength of crushed aggregate base course due to gradational, regional, and source variations - Eggen, Paul; Brittnacher, Don (Wisconsin Highway Research Program, 2004)
This research investigates the range of load-carrying capability, in terms of resilient modulus (MR), of crushed aggregate base course in Wisconsin and how variables, such as physical characteristics, material type, source lithilogy and regional factors influence MR. Testing was conducted on 37 aggregate sources and the results statistically analyzed to look for correlations between MR and these variables and to determine if they could be used to predict MR. Results showed that MR did not differ between and/gravel pit and quarry groups and that carbonate quarries generally gave significantly higher MR values than Precambrian, felsic-plutonic quarries. Changing gradation of base course from a given source affected MR test results, but not consistently or predictably. Certain physical parameters, were found that influence MR in some of the geologic subsets. However, none of the correlations were strong enough to predict MR with sufficient confidence. The test data will provide a base of information that will be useful when WisDOT adopts a mechanistic-empirical pavement design process.
46 p.
Keywords: Base course; Wisconsin; Physical properties; Geology; Laboratory tests; Gradiation; Resilient modulus